Gli strumenti dell'agricoltura di precisione: le mappe di prescrizione per la concimazione - Sara Antognelli (mediaGEO soc. coop., 2021)
Technologies for precision agriculture are spreading over the agricultural world. They include different tools for data gathering, forecasts, prescription, decision and actuation of the decisions. To be effective, farmers should be skilled to use them. The paper shows how, between the several technologies, indices calculated from satellite can be used to create useful prescription maps for optimizing crop fertilization.